Determinants Used to Justify the Strength of Recommendations among Korean Clinical Practice Guidelines - Shin, Ein-Soon; Jang, Ji-Eun; Yeon, Ji-Yun; Kim, Da-sol; Chang, Sung-Goo; Lee, Yoon-Seong (Journal of Korean medical science, 2018)
A standardized systematic approach to grade evidence and the strength of recommendations is important for guideline users to minimize bias and help interpret the most suitable decisions at the point of care. The study aims to identify and classify determinants used to make judgement for the strength of recommendations among 56 Korean clinical practice guidelines (CPGs), and explore strong recommendations based on low quality of evidence. Determinants used in the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach among 34 CPGs which have reported both strength of recommendations and level of evidence were reviewed. Five of 34 CPGs (14.7%) considered quality of evidence, benefits and harms, patients' values and preferences, and costs. And 24 of 34 CPGs (70.6%) considered both magnitude of effect and feasibility as additional determinants. Judgement table was not widely provided for use to translate evidence into recommendations. Eighty-two of 121 recommendations (67.8%, ranged 20.0% to 100.0%) among 11 CPGs using the same judgement scheme showed 'strong' strength of recommendations based on low or very low quality of evidence. Among 5 paradigmatic situations that justify strong recommendations based on low or very low evidence, situation classified as 'potential equivalence, one option clearly less risky or costly' was 87.8% for 82 strong recommendations. Situation classified as 'uncertain benefit, certain harm' was 4.9%. There is a need to introduce and systematize an evidence-based grading system. Using judgement table to justify the strength of recommendations and applying the 5 paradigmatic situations mentioned above is also recommended in the near future.